A consensus on optimization of care in patients with growth hormone deficiency and mild traumatic brain injury. (October 2022) - Yuen, Kevin C.J.; Masel, Brent; Jaffee, Michael S.; O'Shanick, Gregory; Wexler, Tamara L.; Reifschneider, Kent; Urban, Randall J.; Hoang, Sophie; Kelepouris, Nicky; Hoffman, Andrew R.
Abstract: Objective/design: Approximately 2.9 million children and adults in the US experience traumatic brain injuries (TBIs) annually, most of which are considered mild. TBI can induce varying consequences on pituitary function, with growth hormone deficiency (GHD) among the more commonly reported conditions. Panels of pediatric and adult endocrinologists, neurologists, physical medicine and rehabilitation specialists, and neuropsychologists convened in February and October 2020 to discuss ongoing challenges and provide strategies for detection and optimal management of patients with mild TBI and GHD. Results: Difficulties include a low rate of seeking medical attention in the population, suboptimal screening tools, cost and complexity of GHD testing, and a lack of consensus regarding when to test or retest for GHD. Additionally, referrals to endocrinologists from other specialists are uncommon. Recommendations from the panels for managing such patients included multidisciplinary guidelines on the diagnosis and management of post-TBI GHD and additional education on long-term metabolic and probable cognitive benefits of GH replacement therapy. Conclusion: As patients of all ages with mild TBI may develop GHD and/or other pituitary deficiencies, a multidisciplinary approach to provide education to endocrinologists, neurologists, neurosurgeons, traumatologists, and other providers and guidelines for the early identification and management of persistent mild TBI-related GHD are urgently needed. Highlights: Hypopituitarism has been reported following mild traumatic brain injury Increased awareness of this condition after mild traumatic brain injury is needed Growth hormone deficiency in children can cause poor growth velocity Growth hormone deficiency in adults can lead to cognitive and physical impairment Early identification and management of this condition are urgently needed